1973
DOI: 10.1159/000231106
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Heterophile Antigen in Lymphoma and Leukemia Spleens by Means of Absorption of Infectious Mononucleosis Sera

Abstract: Spleen specimens from patients suffering from lymphomas and leukemias were studied for the presence of heterophile antigen by means of absorption of infectious mononucleosis sera. In the lymphoma group, 11 of 16 spleens tested diminished significantly the titer of lysins for bovine red blood cells in infectious mononucleosis sera. The absorbing effect of these spleen specimens correlated well with the replacement of the normal organ structure by malignant cells. None of five spleens from leukemia patients had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1975
1975
1983
1983

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…The precipitin in IM sera was shown to be the P-B antibody and the precip itinogen in syphilis and leprosy sera was shown to be long to the P-B antigenic complex and to be closely related to the previously described B antigen of this complex [5], As mentioned above, in our previous investiga tions [1][2][3][4], we noted P-B antigen in human pathologi cal tissues and sera. In one study [3] we demonstrated the B antigen in 28% of lymphoma-leukemia sera test ed.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…The precipitin in IM sera was shown to be the P-B antibody and the precip itinogen in syphilis and leprosy sera was shown to be long to the P-B antigenic complex and to be closely related to the previously described B antigen of this complex [5], As mentioned above, in our previous investiga tions [1][2][3][4], we noted P-B antigen in human pathologi cal tissues and sera. In one study [3] we demonstrated the B antigen in 28% of lymphoma-leukemia sera test ed.…”
Section: Discussionsupporting
confidence: 53%
“…In spite of the expression of P-B antigens in spleens of patients with lymphoreticular malignan cies [1][2][3] as well as in some cancer tissues [4], no P-B antibody response has been observed in these patients [see the reviews, ref. [14][15][16][17], In our initial study by means of hemagglutination inhibition (HI) tests [4], P-B antigen was found in sera of 5-12% of these pa tients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this connection, it is note worthy that PB antigen appears in mice as a T cell marker [7. 14] and that the spleen of some patients with lymphoma or leukemia contain this antigen [15]. Thus far, the anti gen has not been demonstrated on atypical lymphocytes in peripheral blood of IM pa tients [16],…”
Section: Discussionmentioning
confidence: 99%